The Influence of Workload and Work Stress on Employee Performance at PT Bank BRI Palopo Branch - Apsari, Cintia; Kasran, Muhammad; Dewi, Sari Ratna (PT. EQUATOR SINAR AKADEMIA, 2025)
The purpose of this study was to determine how the performance of PT Bank BRI Palopo Branch employees is affected by workload and work stress. The methodology in this study, such as validity test, reliability test, using SPSS to conduct multiple linear regression analysis, t test, f test, and coefficient of determination test. Participants in this study consisted of all employees of PT Bank BRI Palopo Branch, totaling 53 people. The research sample was determined using the saturated sample technique, where the number of samples was the same as the population, namely 53 people. Data collection was done by distributing questionnaires online through Google Form. The research findings show that workload has a significant and positive effect on the performance of employees of PT Bank BRI Palopo Branch, while work stress has no effect on employee performance in that place. Suggestions to routinely conduct job analysis to ensure the distribution of tasks in accordance with the capacity and competence of each employee.